Perancangan Manajamen Proyek Sistem Informasi Penggajian Karyawan - Maharani Arafah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
An employee payroll information system is an important component in an organization for managing employee salary data and payments effectively and efficiently. This research aims to analyze the factors that influence the success of employee payroll information system project management. The research method used is the waterfall method, which includes planning stages, needs analysis, system design, implementation, as well as testing and evaluation. This system is designed to automate the payroll process, from calculating salaries, withholding taxes, to creating financial reports. With this information system, it is hoped that it can reduce human error in the payroll process and increase employee satisfaction through transparency and accuracy of salary data. Where the implementation results show a significant increase in the speed and accuracy of payroll. Key factors for the success of this project include active involvement of stakeholders, use of appropriate technology, and effective risk management.